Refining the eruption chronology of Atitlán Caldera through zircon double-dating - Cisneros de León, Alejandro; Danišík, Martin; Schmitt, Axel Karl; Schindlbeck-Belo, Julie C.; Kutterolf, Steffen; Mittal, Tushar; Garrison, Jennifer M.; Sims, Kenneth W. W. (Geochemistry, geophysics, geosystems, 2025)
Precise dating of Quaternary volcanism is vital for risk mitigation, understanding volcano-climate interactions, and deciphering the evolution of large silicic magmatic systems. The Atitlán caldera in Guatemala has experienced major eruptions that challenge radiometric dating techniques and complicate eruption chronology in this densely populated area. This study refines the eruptive history of Atitlán caldera using zircon double-dating (ZDD: combined [U-Th]/He and 238U-230Th disequilibrium dating). We present new ZDD eruption ages for previously undated events, including the I-tephra and the newly discovered Atitlán Early Tephra (AET). Additionally, we provide crystallization dates for the Los Chocoyos (LCY) supereruption, utilizing ultra-distal samples from the Pacific Ocean, Lake Petén Itzá, and Mexico. ZDD was also applied to the 40Ar/39Ar sanidine-dated W-tephra confirming its reliability. Our findings yield an internally consistent chronology, with the first radiometric ages of 64 ± 8 ka for the I-tephra and 497 ± 12 ka for AET. The ZDD eruption age of 160 ± 9 ka for W-tephra corroborates the existing 40Ar/39Ar sanidine age. Bayesian eruption age modeling (BEAM) of new LCY 238U-230Th disequilibrium dates consistently yields ages younger than previous estimates based on overdispersed zircon and plagioclase dates. Regardless of the prescribed zircon age distribution, BEAM results indicate the youngest zircon crystallization at ca. 88-76 ka, supporting the established ZDD eruption age of 75 ± 2 ka for LCY. This refined chronology provides insights into the Atitlán caldera volcanic activity, enhances hazard assessment and understanding of regional geological evolution, and highlights the pitfalls of Bayesian age modeling when integrating different chronometers.